New Trainers - Hunt,Roderick (Oxford University press, 1986)
ew Trainers" by Roderick Hunt is a story from the Oxford Reading Tree series that follows the characters as they explore the excitement of getting new trainers. In this tale, the children are thrilled about their new footwear and eager to show them off. As they engage in various activities, they learn about the importance of friendship and teamwork. The story captures the joy and anticipation of new experiences, making it relatable for young readers. With lively illustrations and simple text, it$1 (Bs designed to encourage early reading skills while conveying positive messages about sharing and supporting one another.s
Keywords: Textbook